Some characteristics and functional properties of Chunma (Gastrodia elata) as a food supplement: a short review - Jaswir, I; Octavianti, F; Lestari, W; Hendri, R; Ahmad, H (Univ Putra Malaysia Press, 2024)
Gastrodin elata blume (Tianma in Chinese, Chunma in Korean) is a perennial parasitic herbaceous plant native to Korea, Japan and China (Chae et al., 2008). The plant has recently received very good attention, especially in Korea, due to its excellent health-promoting properties. This plant is reported to have excellent antioxidant, anticancer and anti-inflammatory properties. This paper briefly reviews some characteristics and functional properties of Chunma. (C) All Rights Reserved